2018
DOI: 10.5194/acp-18-8807-2018
|View full text |Cite
|
Sign up to set email alerts
|

The importance of mixed-phase and ice clouds for climate sensitivity in the global aerosol–climate model ECHAM6-HAM2

Abstract: Abstract. How clouds change in a warmer climate remains one of the largest uncertainties for the equilibrium climate sensitivity (ECS). While a large spread in the cloud feedback arises from low-level clouds, it was recently shown that mixed-phase clouds are also important for ECS. If mixedphase clouds in the current climate contain too few supercooled cloud droplets, too much ice will change to liquid water in a warmer climate. As shown by Tan et al. (2016), this overestimates the negative cloud-phase feedbac… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
86
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(88 citation statements)
references
References 95 publications
2
86
0
Order By: Relevance
“…Until recently, this bias has been common to many climate models, due to the lack of supercooled liquid cloud (Bodas‐Salcedo et al, , ). The improvement in the simulation of supercooled liquid cloud is expected to reduce the strength of the negative optical depth feedback in the Southern Ocean (Tan et al, ), although the effect of the reduction of this bias may depend on the climatology of cloud vertical structure of each model (Bodas‐Salcedo, ; Lohmann & Neubauer, ).…”
Section: Package Testing Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Until recently, this bias has been common to many climate models, due to the lack of supercooled liquid cloud (Bodas‐Salcedo et al, , ). The improvement in the simulation of supercooled liquid cloud is expected to reduce the strength of the negative optical depth feedback in the Southern Ocean (Tan et al, ), although the effect of the reduction of this bias may depend on the climatology of cloud vertical structure of each model (Bodas‐Salcedo, ; Lohmann & Neubauer, ).…”
Section: Package Testing Resultsmentioning
confidence: 99%
“…liquid cloud (Bodas-Salcedo et al, 2014, 2016a. The improvement in the simulation of supercooled liquid cloud is expected to reduce the strength of the negative optical depth feedback in the Southern Ocean , although the effect of the reduction of this bias may depend on the climatology of cloud vertical structure of each model (Bodas-Salcedo, 2018;Lohmann & Neubauer, 2018). Figure 5 shows the zonal means of the net cloud feedback and its decomposition into SW and LW components for the two baseline experiments and for combinations of the Mic_On, Aer_On, and Erf_On packages.…”
Section: Package Testing Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We note that the conclusions drawn from the analysis of the results in this study were based on a single climate model and the extent to which our results hold across different climate models has not yet been tested. A recent study investigating the impact of cloud thermodynamic phase partitioning on ECS using the ECHAM6.3‐HAM2.3 model found that the importance of the cloud phase feedback on ECS may be model‐dependent (Lohmann & Neubauer, ). We also point out that we focus on the long‐term (century and longer time scale) impact of SLF on Arctic climate change in our study that occurs after ocean heat adjustment.…”
Section: Discussionmentioning
confidence: 99%
“…Changes and improvements in E63H23 are also described in Lohmann and Neubauer (2018) and Tegen et al (2018) and are 25 repeated here shortly for the convenience of the reader. From ECHAM6.1 to ECHAM6.3 the following improvements were made:…”
Section: Changes and Improvements In E63h23mentioning
confidence: 99%